2016
DOI: 10.1088/1367-2630/18/7/075002
|View full text |Cite
|
Sign up to set email alerts
|

Directed collective motion of bacteria under channel confinement

Abstract: Dense suspensions of swimming bacteria are known to exhibit collective behaviour arising from the interplay of steric and hydrodynamic interactions. Unconfined suspensions exhibit transient, recurring vortices and jets, whereas those confined in circular domains may exhibit order in the form of a spiral vortex. Here we show that confinement into a long and narrow macroscopic 'racetrack' geometry stabilises bacterial motion to form a steady unidirectional circulation. This motion is reproduced in simulations of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
222
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 227 publications
(243 citation statements)
references
References 53 publications
18
222
3
Order By: Relevance
“…A good example of this can be found in microorganisms immersed in a fluid, in which diffusive signalling interactions tend to be short-range, but hydrodynamic couplings can be long-range. This was observed by Lushi et al [94] and Wioland et al [95], who have shown that the reaction to stimuli in swimming bacterial colonies can result not only from the local chemical interactions, as expected, but also from longrange hydrodynamic flows (figure 2). Similar results were presented by Cisneros et al [96].…”
Section: Network With Scale-invariant Node Distancesupporting
confidence: 67%
“…A good example of this can be found in microorganisms immersed in a fluid, in which diffusive signalling interactions tend to be short-range, but hydrodynamic couplings can be long-range. This was observed by Lushi et al [94] and Wioland et al [95], who have shown that the reaction to stimuli in swimming bacterial colonies can result not only from the local chemical interactions, as expected, but also from longrange hydrodynamic flows (figure 2). Similar results were presented by Cisneros et al [96].…”
Section: Network With Scale-invariant Node Distancesupporting
confidence: 67%
“…Intriguingly, the distribution of vorticity in these lattices can be understood using lattice field theory methods well known in statistical physics. In very recent work, we studied these same bacterial suspensions confined to annuli whose width was in the range 10-100 µm and up to several millimetres long (Wioland, Lushi & Goldstein 2016a). Here, if the transverse dimension is sufficiently small there would be spontaneous unidirectional motion around the 'racetrack', but when the channel width exceeded a size comparable to the intrinsic vortex scale (∼70 µm), the mean flow would rapidly vanish.…”
Section: Collective Behaviour In Microswimmer Suspensionsmentioning
confidence: 99%
“…However, when the suspension is enclosed by a small container of dimensions comparable to Λ, individual vortices become stabilized for several minutes [11,12] and can be coupled together to form magnetically ordered vortex lattices [13]. Another form of confinement-induced symmetry breaking was observed recently in a microfluidic realization of bacterial 'racetracks' [14]. For sufficiently narrow tracks of diameter Λ, bacteria spontaneously aligned their swimming directions to form persistent unidirectional currents.…”
mentioning
confidence: 95%